OPTIMIZATION OF THE DISTRIBUTIVE SUPERVISION MODEL TO IMPROVE TEACHER PROFESSIONALISM AT MTS AL-MUSLIM: (Studi Kasus di Madrasah Tsanawiyah Almuslim) - Hajar, Ibnu; Yusrianti, Susi (Idaarah: Jurnal Manajemen Pendidikan, 2024)
This research aims to optimize the distributive supervision model in increasing teacher professionalism at MTs Al-Muslim. A qualitative approach with a case study design was used in this research to explore an in-depth understanding of the implementation of distributive supervision in madrasas. Data was collected through participant observation, in-depth interviews with teachers and school principals, as well as documentation studies. The research results show that the application of distributive supervision improves the quality of teacher teaching through collaboration and joint reflection. Teacher participation in professional development activities also increased significantly from 50% to 80%, and the positive impact on teachers’ emotional well-being was seen through increased self-confidence and motivation in teaching. This research also found that the distributive supervision carried out at MTs Al-Muslim strengthens Islamic values, such as syura (deliberation) and ta’awun (cooperation) which are the basis for managing education in madrasas. This model contributes to innovation by integrating Islamic values ​​in educational supervision. Suggestions put forward for school management include adapting flexible supervision schedules, training for mentors, and supporting educational policies to support wider implementation of this model in Islamic educational institutions.